Are nurse`s needs assessment methods robust enough to recognise palliative care needs in people with dementia? A scoping review - Susanne de Wolf-Linder; Margarete Reisinger; Elisabeth Gohles; Emma L. Wolverson; Maria Schubert; Fliss E. M. Murtagh (BMC, 2022)
Abstract Background People with dementia are most at risk of experiencing serious health related suffering, if they do not have a palliative care approach introduced early enough in the illness. It can be challenging for nurses to assess experienced needs of people, who are thought no longer able to self-report such as people with dementia. Assessment help to understand the care the patient and their family need promptly. It is unknown how nurses recognise holistic palliative care needs in people with dementia during routine care. Methods Scoping review where EMBASE, MEDLINE, CINAHL, PsycInfo databases, and references were searched with an advanced search strategy, which was built on three concepts (nurses, dementia, and nursing assessment) using corresponding Medical Subject Headings. Data were charted in a piloted extraction form, based on the assessment domains within the nursing process followed by summarise and synthesise results narratively. Results 37 out of 2,028 qualitative and quantitative articles published between 2000 and 2021, and relating to 2600 + nurses, were identified. Pain was sole focus of assessment in 29 articles, leaving 8 articles to describe assessment of additional needs (e.g., discomfort). Nurses working in a nursing home assess pain and other needs by observing the persons with dementia behaviour during routine care. Nurses in the acute care setting are more likely to assess symptoms with standard assessment tools at admission and evaluate symptoms by observational methods. Across settings, about one third of pain assessments are supported by person-centred pain assessment tools. Assessments were mostly triggered when the person with dementia vocalised discomfort or a change in usual behaviour was observed. Nurses rely on family members and colleagues to gain more information about needs experienced by people with dementia. Conclusion There is a scarcity of evidence about techniques and methods used by nurses to assess needs other than pain experienced by people with dementia. A holistic, person-centred screening tool to aid real-time observations at the bedside and used in conversations with health care professionals and families/friends, may improve need recognition other than pain, to ensure holistic needs could then be addressed timely to improve care in people with dementia.